2017
DOI: 10.1111/ijd.13823
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of Treponema pallidum PCR in diagnosis of primary and secondary syphilis

Abstract: Background Syphilis remains a major challenge and a complex diagnosis. We aim to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 11 publications
(22 reference statements)
3
19
1
1
Order By: Relevance
“…Among 545 men with at least one TMA test result, the addition of rectal and pharyngeal TMA testing to standard procedures identified 2 extra cases of syphilis, although 1 of those persons would have been treated in the absence of a definitive diagnosis because he presented following known exposure to syphilis. Although we are not aware of prior studies that used T. pallidum NAATs to screen high-risk patients for syphilis, our findings are largely consistent with prior studies showing that 5% to 20% of persons with primary syphilis have negative syphilis serological results but test positive using NAATs of genital lesions (6,13,22,27,28). Similarly, PCR results for blood samples from patients with negative serological results who are evaluated as known syphilis contacts are sometimes positive (23).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among 545 men with at least one TMA test result, the addition of rectal and pharyngeal TMA testing to standard procedures identified 2 extra cases of syphilis, although 1 of those persons would have been treated in the absence of a definitive diagnosis because he presented following known exposure to syphilis. Although we are not aware of prior studies that used T. pallidum NAATs to screen high-risk patients for syphilis, our findings are largely consistent with prior studies showing that 5% to 20% of persons with primary syphilis have negative syphilis serological results but test positive using NAATs of genital lesions (6,13,22,27,28). Similarly, PCR results for blood samples from patients with negative serological results who are evaluated as known syphilis contacts are sometimes positive (23).…”
Section: Discussionsupporting
confidence: 86%
“…The incubation period from the initial Treponema pallidum infection to the development of a chancre, the lesion associated with primary syphilis, is usually said to vary from 10 to 90 days (8), with experimental studies of T. pallidum inoculation suggesting a mean incubation period of 3 to 4 weeks (9,10). The sensitivity of serological testing in primary infections varies widely, i.e., from 50 to 90%, depending on the test used and the population studied (6,7,(11)(12)(13)(14). Thus, in many cases, there is a substantial period between the time of infection and the time at which infections are detectable using available laboratory tests.…”
mentioning
confidence: 99%
“…Matt Shields’ study showed that the sensitivity of routine PCR ranged from 84.6% to 89.1%, and the specificity ranged from 93.1% to 100% for primary syphilis, while in the secondary stage of disease, the sensitivity declined to 50%. This result implied that routine PCR should be used only for early‐stage syphilis, which was supported by Gayet‐Ageron et al However, an other research showed that routine PCR could also be used effectively for secondary syphilis, obtaining a sensitivity and specificity that reached 81.1% and 100%, respectively. Additionally, routine PCR has been reported to detect atypical cases in tonsillar, vertebral, and ocular syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…Specific tests like PCR and IHC are useful supplementary diagnostic tools, PCR test increases the sensitivity of the diagnosis of primary syphilis during the window period, 10 and IHC has shown to be a test with high sensitivity. 35,36 The strength of the present case lies in the clinical, histopathological, and serological findings, which evidence the overlap between the primary stage and secondary stage of oral syphilis in PLWH.…”
Section: Case Descriptionmentioning
confidence: 99%
“…7,8 The VDRL test is cheap and simple to perform but requires confirmation by a treponemal test such as FTA-ABS. 7 False-negative results may be caused by (a) the failure of dysfunctional B-cells to develop an appropriate antibody response against T. pallidum antigens, 9 or (b) the Hook effect or prozone phenomena, a condition present in 0.2% to 2% of PLWH with syphilis, [10][11][12] a consequence of abnormal B-cell activation leading to excess antibody production. 11 In these challenging cases, the confirmation of syphilis diagnosis should be complemented by the direct detection of T. pallidum in tissue specimens using immunohistochemistry (IHC), which has shown a sensitivity of 91%, 13 or by the amplification of the polA gene by polymerase chain reaction (PCR), 10,14,15 an assay with a sensitivity of 95.8% and specificity of 95.7% 16 that has been shown its effectiveness for diagnosing early-stage syphilis.…”
Section: Introductionmentioning
confidence: 99%